PENGEMBANGAN MEDIA INTERAKTIF MENGGUNAKAN QUIZIZZ UNTUK MENINGKATAKAN HASIL BELAJAR SISWA SMPN 1 LAMBITU - Salmawati; Ahyar; Ika Irawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The lack of digital-based learning media used in informatics learning is one of the main problems faced by SMPN 1 Lambitu. This study aims to develop interactive learning media using Quizizz to improve student learning outcomes at SMPN 1 Lambitu. This research is a development research with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The product feasibility test was conducted by two material experts and two media experts. The results of the feasibility test by the media experts showed that the product was included in the Very Feasible category with percentages of 91.43% and 88.57%, respectively, while the results of the feasibility test by the material experts were also in the Very Feasible category with percentages of 87.5% and 90%. The results of the product effectiveness test through pretest and posttest on 20 grade VII students showed an average N-gain of 0.73 which is included in the high category. Therefore, this product is proven to be effective in improving student learning outcomes. These results indicate that the use of Quizizz media can significantly improve student learning outcomes, as well as increase motivation and participation in the learning process. This media also supports the implementation of the Independent Curriculum, which emphasizes active and interactive learning.